2021
DOI: 10.1016/j.xinn.2021.100077
|View full text |Cite
|
Sign up to set email alerts
|

A Static Magnetic Field Improves Iron Metabolism and Prevents High-Fat-Diet/Streptozocin-Induced Diabetes

Abstract: Summary Type 2 diabetes (T2D) is a metabolic disorder with high prevalence and severe complications that has recently been indicated to be treatable by a combined static magnetic field (SMF) and electric field. We systematically compared four types of SMFs and found that a downward SMF of ∼100 mT could effectively reduce the development of hyperglycemia, fatty liver, weight gain, and tissue injury in high-fat-diet (HFD)/streptozocin-induced T2D mice, but not the upward SMF. The downward SMF markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…[7][8][9][10] In contrast to tools such as high pressure and high temperature that require critical experiment conditions, a commercial permanent magnet is enough to influence many chemical reactions. [11,12] For example, an extremely low magnetic field of 55 mT (600 times the magnetic field of earth) can accelerate the catalytic ATP synthesis by 50%. [13] Recently, there has been growing research interest regarding the effects of magnetic interactions on the rate of hydrogen-energy-related reactions such as in water splitting and fuel cells (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In contrast to tools such as high pressure and high temperature that require critical experiment conditions, a commercial permanent magnet is enough to influence many chemical reactions. [11,12] For example, an extremely low magnetic field of 55 mT (600 times the magnetic field of earth) can accelerate the catalytic ATP synthesis by 50%. [13] Recently, there has been growing research interest regarding the effects of magnetic interactions on the rate of hydrogen-energy-related reactions such as in water splitting and fuel cells (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the reductions of ROS levels were found in human peripheral blood neutrophils [ 33 ] and bronchial epithelial cells [ 34 ] when exposed to 60 mT and 389 mT SMFs, respectively. In our previous study, exposure to SMFs of 0.1 T~0.5 T could reduce ROS levels and improve gut microbes, which improved T2D mice [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Van Huizen et al found that weak SMFs could alter stem cell proliferation and differentiation through regulating ROS levels and the downstream heat shock protein 70 [ 16 ]. Recently, two papers both show that SMF or SMF combined with electric field could regulate the redox process and ROS levels, which are essential for their role in alleviating mouse type 2 diabetes [ 17 , 18 ]. However, the effect of SMF on cancer metastasis is unclear and whether SMF could regulate ROS levels to interfere with cancer metastasis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reveal that using SMFs to improve wound healing in diabetes patients seems to have a lot of potential in the future. Moreover, previous studies also show that 100 mT moderate SMF alone or 3 mT moderate SMF combined with electric field could reduce ROS level to reduce blood glucose and significantly alleviate type 2 diabetes (T2D) complications, including fatty liver and renal defects [31,33]. However, whether we can use a specific SMF device to improve diabetic wound healing as well as alleviate other diabetic complications simultaneously is still unknown.…”
Section: Introductionmentioning
confidence: 99%